2017
DOI: 10.1111/petr.12922
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity following pediatric heart transplantation: A systematic review

Abstract: Pediatric HTs account for 13% of all HTs with >60% of recipients surviving at least 10 years post-HT. The purpose of this systematic review is to synthesize the literature on exercise capacity of pediatric HT recipients to improve understanding of the mechanisms that may explain the decreased exercise capacity. Six databases were searched for studies that compared the exercise capacity of HT recipients ≤21 years old with a control group or normative data. Sixteen studies were included. Pediatric HT recipients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…18 More recently, a systematic review looking at six major databases comparing cardiopulmonary exercise tests using treadmill or electronically braked cycle ergometer in children who received heart transplant to a healthy control group found that resting heart rate was higher compared to controls but that peak heart rate, heart rate reserve, peak oxygen consumption, exercise duration, and minute ventilation were significantly lower compared to controls or normative data. 20 In our study, we were unable to compare serial cardiopulmonary exercise tests in this cohort as routine testing was not routinely performed following heart transplant; however, in the last few years, our practice has now incorporated cardiopulmonary exercise testing as an additional clinical test to monitor patients with plans for serial testing every 2-3 years.…”
Section: Discussionmentioning
confidence: 94%
“…18 More recently, a systematic review looking at six major databases comparing cardiopulmonary exercise tests using treadmill or electronically braked cycle ergometer in children who received heart transplant to a healthy control group found that resting heart rate was higher compared to controls but that peak heart rate, heart rate reserve, peak oxygen consumption, exercise duration, and minute ventilation were significantly lower compared to controls or normative data. 20 In our study, we were unable to compare serial cardiopulmonary exercise tests in this cohort as routine testing was not routinely performed following heart transplant; however, in the last few years, our practice has now incorporated cardiopulmonary exercise testing as an additional clinical test to monitor patients with plans for serial testing every 2-3 years.…”
Section: Discussionmentioning
confidence: 94%
“…In favor of the high-intensity interval training group the mean [95% CI] change in peak oxygen consumption between groups was 7.0 [2.6, 11.3] ml/kg/min (p = 0.005) at follow-up (Table 2) also in this study. Maximum muscle strength was also significantly higher in the high-intensity interval training group at follow-up, with a mean [95% CI] difference of 41 [5,77] Newton meters (p = 0.031) (Figure 3), while the difference in muscular exercise capacity was non-significant ( Figure 4).…”
Section: Young Recipients In the Tex-studymentioning
confidence: 99%
“…Little is known about the effect of exercise in young heart transplant recipients, but most of the few studies that exist report benefits in overall exercise capacity as well as improved health-related quality of life. [1][2][3][4][5] Furthermore, the literature demonstrates individuals´ participation and excellent achievements in national and international transplant games; in competitive cycling, in grueling endurance competitions as the Ironman, and in climbing the world´s tallest peaks. 6 Yet, results on group level is lacking, and more research in this area is highly warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the effect of exercise in young heart transplant recipients, but most of the few studies that exist report benefits in overall exercise capacity as well as improved health-related quality of life [1][2][3][4][5]. Furthermore, the literature demonstrates individuals' participation and excellent achievements in national and international transplant games; in competitive cycling, in grueling endurance competitions as the Ironman, and in climbing the world's tallest peaks [6].…”
Section: Introductionmentioning
confidence: 99%